NS2B-3 proteinase-mediated processing in the yellow fever virus structural region: in vitro and in vivo studies. - Amberg, S M (1994)
Several of the cleavages required to generate the mature nonstructural proteins from the flaviviral polyprotein are known to be mediated by a complex consisting of NS2B and a serine proteinase domain located in the N-terminal one-third of NS3. These cleavages typically occur after two basic residues followed by a short side chain residue. Cleavage at a similar dibasic site in the structural region is believed to produce the C terminus of the virion capsid protein. To study this cleavage, we developed a cell-free trans cleavage assay for yellow fever virus (YF)-specific proteolytic activity by using a substrate spanning the C protein dibasic site. Cleavage at the predicted site was observed when the substrate was incubated with detergent-solubilized lysates from YF-infected BHK cells. NS2B and the NS3 proteinase domain were the only YF-specific proteins required for this cleavage. Cell fractionation studies demonstrated that the YF-specific proteolytic activity was membrane associated and that activity could be detected only after detergent solubilization. Previous cell-free studies led to a hypothesis that processing in the C-prM region involves (i) translation of C followed by translocation and core glycosylation of prM by using an internal signal sequence, (ii) signalase cleavage to produce a membrane-anchored form of the C protein (anchC) and the N terminus of prM, and (iii) NS2B-3-mediated cleavage at the anchC dibasic site to produce the C terminus of the virion C protein. However, the results of in vivo transient-expression studies do not support this temporal cleavage order. Rather, expression of a YF polyprotein extending from C through the N-terminal one-third of NS3 revealed that C-prM processing, but not translocation, was dependent on an active NS2B-3 proteinase. This suggests that signalase-mediated cleavage in the lumen of the endoplasmic reticulum may be dependent on prior cleavage at the anchC dibasic site. Possible pathways for processing in the C-prM region are outlined and discussed.